KAJIAN PENGGUNAAN LIMBAH SERAT DAUN NANAS DAN LIMBAH PLASTIK PADA KUAT LENTUR PELAT BETON TIPIS - Ramlan; Sarif, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
This study aims to obtain the flexural tensile strength of thin concrete slabs with the composition of the constituent materials in the form of plastic pellets as a substitute for aggregate and pineapple leaf waste fiber as a substitute for tensile reinforcement. The test carried out is testing the flexural tensile strength of thin concrete slabs with LDPE plastic pellets as a substitute for aggregate without and with pineapple leaf waste fiber to bear the flexural tensile strength due to bending moments placed on two supports. Sample testing was carried out after soaking the sample for 28 days using a bending test machine. The results of testing the flexural tensile strength of thin concrete slabs with LDPE plastic pellets as a substitute for aggregate (without reinforcement) obtained an average flexural tensile strength of 1.150 MPa. While the flexural tensile strength of thin concrete slabs with LDPE plastic pellets as a substitute for aggregate and pineapple leaf waste fiber as a substitute for reinforcement, the average flexural tensile strength of concrete is 1.476 MPa. The addition of pineapple leaf waste fiber as a substitute for reinforcement provides an increase in the flexural tensile strength of concrete by 22.11% from before